Rescate de la identidad cultural desde estrategias literarias - Shakira Maribel, Cambizaca Ortiz (2024)
The objective of the present investigation was the rescue of cultural identity from literary strategies in the students of the Cicalpa Educational Unit located in the parish of Sicalpa in the province of Chimborazo, through observation and experience, the loss could be evidenced and the devaluation of the culture of its people with acculturation by the dominant culture. That is why we worked on relevant themes aimed at their culture through the selection and adaptation of literary strategies. After the students' active participation, they strengthened their selfesteem, knowledge, and appreciation of traditions, customs, language, and clothing belonging to their culture. The research was based on a qualitative, non-experimental, descriptive, field, documentary, and bibliographic approach by obtaining information from truthful and reliable sources. We worked through data collection techniques in focus groups, followed by the relationship, analysis, and triangulation of data, strengthening the rescue of cultural identity in seventh-grade students of Basic General Education through the presentation and development of literary strategies oriented to the student's cultural context